Triple whammy blues; trial by publicity; mad about sting [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Deals with the one-peso-levy on oil and gasoline in 1994; the controversial issue of the Elsa Castillo film show; and the exclusive interview with rock singer and musician, Sting.
Contents: Triple whammy blues (20 min.) -- Trial by publicity (15 min.) -- Mad about Sting (15 min.)
VHS.
Keywords: Sting -- Interviews; Petroleum products -- Prices -- Philippines; Motion picture plays -- History and criticism. -- Philippines